Minimum water exchange spares the requirement for dietary methionine for juvenile Litopenaeus vannamei reared under intensive outdoor conditions. (29th January 2018) - Façanha, Felipe Nobre; Sabry‐Neto, Hassan; Figueiredo‐Silva, Claudia; Oliveira‐Neto, Adhemar Rodrigues; Nunes, Alberto Jorge Pinto
Abstract: We examined if minimum water exchange could spare dietary methionine (Met) required for maximum growth performance of juvenile Litopenaeus vannamei reared in an intensive outdoor system. Shrimp of 1.98 ± 0.13 g were stocked at 70 animals/m 2 and reared for 72 days in 50 tanks of 1 m 3 under flow‐through (14.4% a day) and static (1.4%–2.9% a day) green‐water conditions at 32.0 ± 3.7 g/L salinity. Five diets with a minimum inclusion of fishmeal supplemented with a dipeptide, dl ‐methionyl‐dl ‐methionine, were formulated to contain increasing levels of Met, 4.8, 6.2, 7.2, 8.1 or 9.4 g/kg (on a dry matter basis). Each of the five diets were fed four times daily to five replicate groups. Dietary Met and water exchange significantly influenced shrimp survival, gained yield, apparent feed intake, food conversion ratio and final body weight ( p < .05). Raising shrimp under limited water exchange, i.e., static versus flow‐through spared the dependence on higher levels of dietary Met to maximize shrimp body weight, from 9.4 g/kg to 8.0 g/kg (14.0 and 12.6 g/kg Met+Cys respectively). In an intensive rearing system, a reduction in water exchange is desirable as it leads to a lower need for supplemental dietary Met.